CRISPR-Cas9 targeting the blaKPC gene in a clinical isolate of Klebsiella michiganensis: Reduction of imipenem resistance and changes in genomic carbapenem resistance determinants - Thaysa Leite Tagliaferri; Alex Krüttgen; Tiago Antonio de Oliveira Mendes; Simone Gonçalves dos Santos; Hans-Peter Horz (PLoS ONE, 2025)
The CRISPR-Cas technology can be used to disable drug resistance genes. Since carbapenem resistance can be mediated by multiple resistance determinants, we here investigated the extent of re-sensizitation when targeting the blaKPC carbapenemase gene and assessed possible effects on porins and efflux pumps. While full re-sensitization was achieved in a laboratory strain of Escherichia coli solely equipped with blaKPC, resistance reduction in a clinical isolate of Klebsiella michiganensis was achieved in 63% of analyzed transformants, which was a consequence of plasmid copy number reduction and decreased blaKPC gene expression. Damages in the Cas9, as well as alterations in carbapenem-resistance promoting genes including ompK36 downregulation and mutations in the acrB gene were found, likely preventing more efficient re-sensitization. Hence, interference with a single resistance gene promoted the emergence of clonal variants that exhibit alterations in outer membrane proteins. Those bacterial countermeasures, however, were not sufficient to restore the original carbapenem-resistant phenotype.